Doing practice-based research in therapy a reflexive approach - Bager-Charleson, Sofie 1959- (SAGE, 2014)
Learning how to use critical self-reflection creatively when practising therapy is an important component of training. This level of self-awareness is, however, often neglected in research, despite the centrality of the researcher to their work. Learning how to use critical self-reflection creatively when practising therapy is an important component of training. This level of self-awareness is, however, often neglected in research, despite the centrality of the researcher to their work. This book makes the vital link between practical research skills and self-awareness, critical reflection and personal development in practice-based research. Starting with a clear introduction to the theory, practice and debates surrounding this type of research, the book then guides the reader step-by-step through the practicalities of the research process, encouraging them to reflect upon and evaluate their practice at each stage. The book: Incorporates five recurring case studies to illustrate different methodological approaches ; Uses real life examples from students conducting practice-based psychotherapy research ; Includes exercises, chapter objectives, end-of-chapter questions and suggestions for further reading to help consolidate learning ; Encourages ongoing personal development by introducing personal development planning (PDP) and lifelong learning in the field of research. By demystifying the reflexive approach, this practical guide ensures that trainees and qualified therapists get the most, both professionally and personally, from their practice-based research. --